2012
DOI: 10.1007/s00705-012-1281-3
|View full text |Cite
|
Sign up to set email alerts
|

Heterologous expression of viral suppressors of RNA silencing complements virulence of the HC-Pro mutant of clover yellow vein virus in pea

Abstract: Many plant viruses encode suppressors of RNA silencing, including the helper component-proteinase (HC-Pro) of potyviruses. Our previous studies showed that a D-to-Y mutation at amino acid position 193 in HC-Pro (HC-Pro-D193Y) drastically attenuated the virulence of clover yellow vein virus (ClYVV) in legume plants. Furthermore, RNA-silencing suppression (RSS) activity of HC-Pro-D193Y was significantly reduced in Nicotiana benthamiana. Here, we examine the effect of expression of heterologous suppressors of RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 33 publications
1
6
0
Order By: Relevance
“…The GST-fused PIPO was produced and subjected to SDS-PAGE as described above. The band, which migrated at around 33 kDa, was specifically detected by immunoblotting with the antibody as described previously (48), indicating that this antibody is able to detect PIPO (see Fig. 6B).…”
Section: Construction Of Chimeric Viruses and P3 Transient Expressionsupporting
confidence: 70%
See 1 more Smart Citation
“…The GST-fused PIPO was produced and subjected to SDS-PAGE as described above. The band, which migrated at around 33 kDa, was specifically detected by immunoblotting with the antibody as described previously (48), indicating that this antibody is able to detect PIPO (see Fig. 6B).…”
Section: Construction Of Chimeric Viruses and P3 Transient Expressionsupporting
confidence: 70%
“…Uninoculated upper leaves with symptoms were harvested at 9 dpi, ground in liquid nitrogen, and denatured in 12-fold (wt/vol) urea denaturing buffer containing 4.5 M urea, 1% (vol/vol) Triton X-100, 0.5% dithiothreitol (DTT), 0.00625 M Tris-HCl (pH 6.8), 2% (wt/vol) SDS, 5% mercaptoethanol, 5% sucrose, and 0.002% bromophenol blue. The plant lysates were analyzed by SDS-PAGE, as described by Atsumi et al (48).…”
Section: Construction Of Chimeric Viruses and P3 Transient Expressionmentioning
confidence: 99%
“…1G). In previous studies, we revealed that the HC-Pro gene is indirectly involved in the induction of lethal systemic cell death in PI 118501 (20,22,32). We found that a Cl-No.30 mutant with a D-to-Y substitution at amino acid position 193 of HC-Pro (Cl-D193Y) loses the ability to induce cell death in PI 118501 (20).…”
Section: Discussionmentioning
confidence: 92%
“…Western blots were conducted as described previously (30,32). Proteins were resolved in 12% NuPAGE Bis-Tris gels (Thermo Fisher Scientific) using MES-SDS buffer (FLAG-tagged protein detection) or in 10% SDS-PAGE using Tris-glycine buffer (coat protein [CP] detection [33]), followed by electrotransfer onto a polyvinylidene difluoride (PVDF) membrane.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation